2020
DOI: 10.1002/qua.26569
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics study of the structure and supramolecular organization in mesogenic lanthanum(III) complexes with β‐diketones and Lewis bases

Abstract: Simulation technique for the study of the structural properties and supramolecular organization of mesogenic lanthanum(III) complexes with β‐diketones and Lewis bases with the combination of high‐level quantum chemical methods and ab initio molecular dynamics was proposed and approved. Three representatives of La(III) complexes with ligands of various nature were investigated and relations between their structural properties and liquid‐crystalline (LC) behavior were studied. It has been shown that the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 63 publications
(112 reference statements)
0
7
0
4
Order By: Relevance
“…Furthermore, the more rigid geometry of Phen ligand compared to Bpy 17-17 increases the emission efficiency of complexes with Phen by minimizing the contribution of nonradiative deactivation to the energy transfer process. At the same time, complexes 1 and 3 with Bpy 17-17 have the highest anisotropy parameters above the LC properties demonstration threshold [8,9,11,27] due to alkyl substituents in Lewis base and βdiketones.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, the more rigid geometry of Phen ligand compared to Bpy 17-17 increases the emission efficiency of complexes with Phen by minimizing the contribution of nonradiative deactivation to the energy transfer process. At the same time, complexes 1 and 3 with Bpy 17-17 have the highest anisotropy parameters above the LC properties demonstration threshold [8,9,11,27] due to alkyl substituents in Lewis base and βdiketones.…”
Section: Discussionmentioning
confidence: 91%
“…Ligands with long alkyl substituents increase this ratio for LC Ln(III) complexes in comparison with other Ln(III) complexes to maximum value of 3.5. [8,9,11,27] According to our earlier studies and calculations, [8,9,11,27] the minimum value of the anisotropy parameter at which mesogenic Ln(III) complexes have LC properties equals 2.5. In this study, the anisotropy of geometry equals According to experimental studies of these compounds, [9,30,56] only complexes with Bpy One of the pioneer studies of mesogenic rare-earth complexes with Schiff base ligands [57] showed that the chain length in ligands has a little influence on the first coordination sphere of Ln(III) ion but determines the packing of complexes in the crystal structure.…”
Section: Optimized Geometries Of the Ground Statementioning
confidence: 89%
See 3 more Smart Citations